2017
DOI: 10.1097/md.0000000000006302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of a centric relation occlusal splint and intra-articular liquid phase concentrated growth factor injection for the treatment of temporomandibular disorders

Abstract: The agony that accompanies the incidence and symptoms of temporomandibular disorders (TMDs) is an important concern in the oral and maxillofacial region. The objective of this study was to explore the clinical findings after centric relation occlusal splint (CROS) treatment and intra-articular injection treatment with liquid phase concentrated growth factors (LPCGFs) in patients with disc displacement without reduction (DDWOR).The group under investigation of this retrospective cohort study included patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
(31 reference statements)
1
24
0
Order By: Relevance
“…Our deduction has been verified in a single-arm study by our research group. [ 15 ] In that study, PRP treatment for TMDs showed satisfactory performance in improving joint sounds, as evidenced by the data that an injection of 2 mL of PRP improved the joint sounds of 23 joints (63.9%) at 12.06 ± 8.54 days after treatment and 26 joints (72.2%) at 48.5 ± 64.1 days after treatment, with no significant relapse of symptoms observed during a follow-up period of 258 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our deduction has been verified in a single-arm study by our research group. [ 15 ] In that study, PRP treatment for TMDs showed satisfactory performance in improving joint sounds, as evidenced by the data that an injection of 2 mL of PRP improved the joint sounds of 23 joints (63.9%) at 12.06 ± 8.54 days after treatment and 26 joints (72.2%) at 48.5 ± 64.1 days after treatment, with no significant relapse of symptoms observed during a follow-up period of 258 days.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In recent years, several studies have reported the use of PRP in intra-articular injection to treat temporomandibular disorders (TMDs), which achieved satisfactory outcomes. [ 1 , 6 , 10 15 ] However, the treatment methods used in these studies were inconsistent, with some using PRP alone and some using arthrocentesis plus PRP (A+PRP). In addition, these studies mostly used traditional PRP in varying doses, from 0.5 to 2 mL, and with different frequencies, from a single injection to 4 injections.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained by Giacomello et al [16], who also obtained an improvement in the range of mandibular lowering motion in the treatment of disc dislocation without reduction and the dimensions before and after the treatment significantly varied statistically. Additionally, Delayme et al [11], Ferrnandez-Ferro et al [26], and Yang et al [21] applied PRP with a beneficial effect on the functioning of the TMJs.…”
Section: Discussionmentioning
confidence: 99%
“…These differences concern the number of revolutions, centrifugation time, preparation of PRP, and the method of injection in the TMJ area. Studies of TMJ injections with PRP and HA have focused on decreased pain after injection in patients with both pain and limited mouth opening, secondary to displacement of the disc without reduction, and other clinical problems, such as arthritis and capsulitis [7,10,12,14,18,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation